PENERAPAN HEUTAGOGY LEARNING DALAM PROGRAM MBKM DI PTKIS - Sutisna; R. Suyato Kusumaryono; Juwita Ramadani Fitria; Anjani Putri Belawati Pandiangan; Norsyam Amaly (Fakultas Agama Islam Universitas Wiralodra, 2022)
THE IMPLEMENTATION OF HEUTAGOGY LEARNING IN THE MBKM PROGRAM IN PTKIS The study's goal is to learn about the main points of MBKM policies, learning activities